How EFL Pre-Service Teachers Negotiate Their Professional Identities During Teaching Practicum: A Narrative Inquiry - Ubaidillah, M. Faruq; Sonny Elfiyanto; Andri Jamaul Rifiyani; Nena Akmaliah Arroudloh (Langkawi: Journal of The Association for Arabic and English, 2026)
This study investigates how EFL pre-service teachers in Indonesia construct and negotiate their professional identities during the teaching practicum. Employing a narrative inquiry approach, it captures participants’ lived experiences during their transition from language learners to novice teachers. Data were collected through in-depth interviews and were analyzed using thematic narrative analysis. The findings show that identity construction is a dynamic and recursive process shaped by personal motivations, classroom interactions, institutional contexts, mentorship, and reflective practice. Initial motivations, such as familial influence, job security, and interest in English, shaped early teaching identities but were often challenged during practicum experiences. Participants encountered classroom realities such as disengaged students, limited resources, curriculum misalignment, and varied mentorship support, which triggered critical reflection and adaptive teaching strategies. Through continuous reflection and classroom engagement, participants negotiated tensions between theoretical knowledge and practical demands, gradually reshaping their pedagogical beliefs and professional self-concepts. Classroom interactions and mentorship experiences emerged as key sites of identity negotiation, enabling participants to develop more flexible and responsive teaching approaches. The study suggests that the teaching practicum functioned as a transformative space for professional identity development.